Studi Pemanfaatan Limbah Sawit Sebagai Bahan Bakar PLTU Biomassa Di Kabupaten Landak - Suharnoto, Ya’ (ELKHA : Jurnal Teknik Elektro, 2017)
Abstract– Currently the main products of oil palm are mainly used as the producer of vegetable oil. The waste originally becoming problems for environment can be used as renewable energy. One of the solutions is by making use of oil palm waste as the fuel of Steam Power Plant. The objective of this thesis is to identify the number of production of fresh fruit branch and waste generated as well as to calculate the potential energy of oil palm waste as the fuel of Biomass Steam Power Plant. The solid wastes of oil palm studied were fibre and shell. Every ton of fresh fruit branch produced 13% fibre with the energy of 2,637 kCal/kg and 6.5% shell with the energy of 4,105 kCal/kg. The area of oil palm plantations that have already had plantation business permit in Landak District is 451,903.06 Ha. The research results show that the potential fibre and shell that can produced by 5 oil palm factories in Landak District, with the production capacity of 225 Ton TBS/hour during the last 6 years until 2016 reached 344,490,729 tons. The potential energy produced is 1,240,590,477 MWh. Based on the Regulation of the Minister of Energy and Mineral Resources No. 12 of 2017 on the Use of Renewable Energy for the Provision of Power, the basic cost of power plant for West Kalimantan Area is 1,406.75. Therefore, the remaining energy ready to use or sell (excess power) after reduced by the factory use is 1,186,885,214 MWh, and the estimated revenue from power sale generated by 5 units of oil palm factories is Rp 1,669,650,774,795. From five samples of oil palm factories, it can be used to estimate the potential energy from oil palm waste in the entire area of Landak District, based on the plant area that can produce the yield and not produce the yield yet. Therefore, the oil palm area of 113,800.59 Ha, it can be produced estimated potential energy of 2,033,268,169 kWh/year and estimated revenue of Rp 2,860,299,996,037,-. The potential energy from oil palm waste will increase year by year along with the increasing procution capacity, oil palm plantation area and increasing oil palm factory construction so that it can increase energy diversification in Landak District. Keywords– Renewable Energy, Shell, Fibre, Fresh Fruit Branch, CPO, Steam Power Plant, Power Energy